2007
DOI: 10.1212/01.wnl.0000265589.32060.d3
|View full text |Cite
|
Sign up to set email alerts
|

Emotional reactivity and emotion recognition in frontotemporal lobar degeneration

Abstract: The socioemotional decline typically seen in frontotemporal lobar degeneration patients may result more from an inability to process certain emotions in other people than from deficits in emotional reactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
93
1
3

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(109 citation statements)
references
References 34 publications
12
93
1
3
Order By: Relevance
“…In terms of emotional responses, participants displayed some emotions when describing events that directly appertained to them, but not in relation to their interactions with others. These subjective experiences are consistent with the findings that people with bvFTD, rather than showing a global impairment in the expression of emotion, are able to express simple emotions such as happiness, sadness and fear (Levenson & Miller, 2007;Werner et al, 2007) shown to be mediated by a neural circuit including the frontal lobes. In a similar vein, people with bvFTD have been found to have an impaired ability to recognise emotions, particularly negative emotions in others (Rankin et al, 2006;Werner et al, 2007) which might be reflecting in some participants' experiences of feeling that they might be doing something wrong but without being able to work out what this might be.…”
Section: Discussionsupporting
confidence: 86%
“…In terms of emotional responses, participants displayed some emotions when describing events that directly appertained to them, but not in relation to their interactions with others. These subjective experiences are consistent with the findings that people with bvFTD, rather than showing a global impairment in the expression of emotion, are able to express simple emotions such as happiness, sadness and fear (Levenson & Miller, 2007;Werner et al, 2007) shown to be mediated by a neural circuit including the frontal lobes. In a similar vein, people with bvFTD have been found to have an impaired ability to recognise emotions, particularly negative emotions in others (Rankin et al, 2006;Werner et al, 2007) which might be reflecting in some participants' experiences of feeling that they might be doing something wrong but without being able to work out what this might be.…”
Section: Discussionsupporting
confidence: 86%
“…Previous bvFTD studies have emphasized the role of right hemisphere degeneration in producing the characteristic clinical features of loss of empathy (65), social disinhibition (66), and overeating (67), perhaps by undermining negative emotions such as embarrassment (68) and visceral feelings such as satiety (67). Simple positive emotions are often preserved, at least at the group level, in heterogeneous bvFTD samples (27,69). Our study provides the more nuanced view that relative injury to the dominant hemisphere autonomic control structures produces a clinical picture that includes reduced parasympathetic outflow and a more irritable, irascible (i.e., less agreeable) patient.…”
Section: Localization and Lateralization Of Cortical Cardiac Parasympmentioning
confidence: 99%
“…1073/pnas.1509184113/-/DCSupplemental. of social-emotional functions and diminished phasic autonomic responses during social-emotional tasks (26,27). Anatomically, bvFTD involves degeneration of core salience network structures proposed to support autonomic regulation, including the ACC and anterior midcingulate cortex (aMCC), FI, and subcortical, limbic, and brainstem sites (28,29).…”
mentioning
confidence: 99%
“…A significant role for the right amygdala in recognition of negative facial affect has also been reported (Rosen, PaceSavitsky et al, 2004). Werner et al (2007) examined two aspects of emotional processing (emotional reactivity and emotion recognition) in FTLD subjects using measures of selfreported emotional experience, emotional facial behavior, autonomic nervous system response to film stimuli, ability to identify a target emotion of fear, happy, or sad experienced by film characters. FTLD patients were significantly impaired compared with controls in emotion recognition for the fear and sad film clips.…”
Section: Contributions To Cognitive Neurosciencementioning
confidence: 99%